Prior Consulting, Mining and Environmental Regulation in the National Legislation - Lanegra Quispe, Iván (2014)
This article describes and analyzes the national standard established for the prior consultation proceedings in mining and its relationship with environmental law. These procedures have been created in order to comply with the liability contracted by the Peruvian State in 1995, after the ratification of ILO Convention 169. The article reviews the main elements of Peruvian prior consulting process, including key aspects such as the identification of indigenous peoples, as well as defining the moment at which consulting should be made in the mining area. Finally, the author stresses the no consultations in mining projects at the time and the implications of that fact.